Articulatory effects on perceptions of men’s status and attractiveness - Sethu Karthikeyan; David A. Puts; Toe Aung; Jennifer K. Link; Kevin Rosenfield; Alexander Mackiel; Allisen Casey; Kaelyn Marks; Michele Cristo; Jenny Patel; Aliza Santos; Glenn Geher (Scientific Reports, 2023)
Abstract Research on heterosexual mating has demonstrated that acoustic parameters (e.g., pitch) of men’s voices influence their attractiveness to women and appearance of status and formidability to other men. However, little is known about how men’s tendency to clearly articulate their speech influences these important social perceptions. In the current study, we used a repeated-measures design to investigate how men’s articulatory clarity or conformity influenced women’s (N = 45) evaluations of men’s attractiveness for both short- and long-term relationships, and men's (N = 46) evaluations of physical formidability and prestige. Results largely supported our hypotheses: men who enunciated phonemes more distinctly were more attractive to women for long-term relationships than short-term relationships and were perceived by other men to have higher prestige than physical dominance. These findings suggest that aspects of articulatory behavior that influence perceptions of prestige and long-term mating attractiveness may indicate an early social history characterized by high socioeconomic status, likely owing to crystallization of articulatory patterns during the critical period of language development. These articulatory patterns may also be honest signals of condition or disposition owing to the nature of complex, multicomponent traits, which deserve further empirical attention.